Pemanfaatan Data Mining Untuk Penempatan Buku Di Perpustakaan Menggunakan Metode Association Rule - Robi Yanto; Hendra Di Kesuma (JATISI (Jurnal Teknik Informatika dan Sistem Informasi), 2017)
Data Mining is the process of analyzing data to find a pattern of hidden data collection. by utilizing the traffic data library, can dig up information about what books are often borrowed by visitors and interrelationships of each loan to be able to do the preparation and layout of the book. In the system that runs the placement of books done by category of books available pad superbly wine book but has not been regulated by intensitasi lending done by members of so many old books are still available in the library. To be able to guide the placement in accordance with the needs of member needs to do a book-lending data processing by using aloritma appriori through the application of methods Associaton rule in order to know the support and confidance between books that are often borrowed so that it can be seen buku.Dibandingkan pattern placement system ongoing performance information is shown on the effectiveness of the system of determining the placement pattern books for book layout and make it easier to determine the existence of the book in this case is based on 3 itemset books.